HISTORIOGRAPHIC ASPECTS OF MEN’S APPAREL DESIGN EVOLUTION - Навольська, Л. В. (Art and Design, 2020)
Systematization of the basic principles of men’s apparel design evolution, depending on historical, social and cultural aspects, analysis of factors of design modification, substantiation of the logic of changes, determining the degree of their relevance in the future. The research includes the analysis of publications on the chosen topic, analytical processing, systematization of the information base collected in the course of research with illustrative material on men’s clothing. The work uses visual and graphic methods of data processing, which make it possible to clearly illustrate the specifics of combining traditional silhouettes and elements of culture. The evolution of men’s apparel design is analyzed on the example of a classical suit: the cyclical nature of men’s apparel design has been confirmed – changes in the design are shown as the reproduction of the same apparel with minor corrections required by the corresponding epoch in the interinfluence of its concept and function. It has been revealed that artistic and aesthetic tastes of each epoch in the history of humanity are best reflected in the men’s apparel, which is also interrelated with the studies on the evolution of military apparel design. The research made it possible to determine the main stages and regularities in the evolution of design of men’s clothing, trends in the logic of the creative process of the apparel design. The logic of changes in the design of men’s apparel has been systematized and structured, taking into account the concept of design, ergonomic, structural and technological aspects. Practical relevance of the obtained results lies in making it possible to simulate creative processes of designing men’s apparel.